Pengaruh Akuntabilitas dan Pengawasan Fungsional Terhadap Pengelolaan Keuangan Daerah (Studi Empiris pada DPKD Kota di Sumatera Barat) - Putri Srie Handayani (Universitas Batanghari Jambi, 2021)
The purpose of this study was to determine the effect of Accountability and Functional Supervision on Regional Financial Management at the city Regional Financial Management Office (DPKD) in West Sumatera. This research is a type of quantitative research. The population in this study is the City Regional Financial Management Office (DPKD) in West Sumatera Province. The sampling method used judgement sampling as many as 4 cities, namely Padang, Padang Panjang, Bukittingi, and Payakumbuh and 250 DPKD employees as respondents. Data was collacted by distributing questionnaires directly to the 250 employees. The data analysis technique used multiple linear regression with t test. The result showed that Accountability and Functional Supervsion had an effect on Regional Financial Management.